Sosialisasi penanganan stunting melalui program satu kelor untuk rumah anda (SAKURA) - Nuryani, Dina Dwi; Mawardi, Qholik; Mahendra, M. Reza; Sundari, Sundari; Tambunan, Bella Aldamar; Dwiyanti, Dea Okta; Pasha, Ketut Indah Ayu (JOURNAL of Public Health Concerns, 2026)
Background: The moringa plant (Moringa oleifera) is widely known for its numerous health, nutritional, and economic benefits. Its leaves contain various essential nutrients, such as vitamin A, vitamin C, calcium, iron, and high levels of antioxidants, which play a vital role in preventing malnutrition, boosting immunity, and supporting family health. Through the "One Moringa for Your Home" program in Way Gelang Village, fieldwork students conducted outreach activities and demonstrated the use of moringa plants. Purpose: To raise public awareness of the importance of moringa leaves as a source of family nutrition and to encourage self-reliance in meeting nutritional needs through planting moringa in home gardens. Method: This community service program was implemented on August 16, 2025, at the Way Gelang Village Hall, West Kota Agung District, Tanggamus Regency, involving 36 community members, health cadres, housewives, and village officials as the main partners. The implementation method used an educational approach, socialization, training, mentoring, and community awareness to increase the use of moringa plants in stunting prevention efforts based on local potential. Socialization was delivered through presentations, educational video screenings, and interactive discussions. Evaluation was carried out in a participatory manner through observation of participant involvement and the success of making processed moringa products. As a form of support for the sustainability of the program and encouragement for the community to continue planting moringa in their yards by forming a small group to monitor the moringa planting movement, which functions as a forum for routine monitoring and evaluation with the village government and health cadres. Results: Most people are familiar with the moringa plant, which commonly grows in gardens, but only a small percentage understand that moringa leaves are a good source of nutrition for families. Training and mentoring demonstrated an increase in community motivation and ability to process and cultivate moringa. The distribution of moringa seeds and hands-on practice fostered psychological support and a sense of community togetherness in meeting nutritional standards more economically. Observations from this activity indicate that the community understands the benefits of the moringa plant and is able to process it into various nutritious food products. Conclusion: Community service activities, including education and live demonstrations on the use of Moringa leaves, have been shown to have a positive impact on increasing nutritional awareness and community skills in utilizing Moringa as an economical and sustainable local food source for stunting prevention. Through nutrition education and training in moringa-based food processing, community motivation and behavior change led to healthier food consumption and increased family food security. Suggestion: While program sustainability still requires mentoring and monitoring, it is hoped that the SAKURA program or similar educational programs can become effective models for community-based nutrition interventions in reducing the risk of stunting and improving family health. Keywords: Family nutrition; Health education; Moringa plants; Stunting prevention Pendahuluan: Tanaman kelor (Moringa oleifera) dikenal luas sebagai tanaman yang kaya manfaat dari segi kesehatan, gizi, dan ekonomi. Daunnya mengandung berbagai nutrisi penting seperti vitamin A, vitamin C, kalsium, zat besi, dan antioksidan tinggi yang berperan penting dalam mencegah kekurangan gizi, meningkatkan daya tahan tubuh, serta menunjang kesehatan keluarga. Melalui program “Satu Kelor untuk Rumah Anda (SAKURA)” di Pekon Way Gelang, mahasiswa Kuliah Kerja Lapangan (KKL) melaksanakan kegiatan sosialisasi dan demonstrasi pemanfaatan tanaman kelor. Tujuan: Untuk meningkatkan kesadaran masyarakat terhadap pentingnya daun kelor sebagai sumber gizi keluarga, serta mendorong kemandirian dalam memenuhi kebutuhan nutrisi melalui penanaman kelor di pekarangan rumah. Metode: Program pengabdian masyarakat ini dilaksanakan pada tanggal 16 Agustus 2025 bertempat di Balai Pekon Way Gelang, Kecamatan Kota Agung Barat, Kabupaten Tanggamus, dengan melibatkan 36 warga masyarakat, kader kesehatan, ibu rumah tangga, dan perangkat Pekon sebagai mitra utama. Metode pelaksanaan menggunakan pendekatan pendidikan, sosialisasi, pelatihan, pendampingan, dan penyadaran masyarakat untuk meningkatkan pemanfaatan tanaman kelor dalam upaya pencegahan stunting berbasis potensi lokal. Sosialisasi disampaikan melalui presentasi, pemutaran video edukasi, dan diskusi interaktif. Evaluasi dilakukan secara partisipatif melalui pengamatan terhadap keterlibatan peserta dan keberhasilan pembuatan produk olahan kelor. Sebagai bentuk dukungan keberlanjutan program dan dorongan bagi masyarakat untuk terus menanam kelor di pekarangan rumah dengan membentuk  kelompok kecil pemantau gerakan tanam kelor, yang berfungsi sebagai wadah monitoring dan evaluasi rutin bersama pemerintah Pekon serta kader kesehatan. Hasil: Sebagian besar masyarakat sudah mengenal tanaman kelor yang biasa tumbuh di areal kebun dan hanya sebagian kecil masyarakat yang memahami bahwa daun kelor merupakan sumber nutrisi yang cukup baik bagi pemenuhan gizi keluarga. Setelah pelatihan dan pendampingan menunjukkan terdapat peningkatan motivasi masyarakat dan kemampuan masyarakat dalam praktik pengolahan dan budidaya kelor. Pembagian bibit kelor dan praktik langsung dalam penerapannya, memberikan semangat pskologis dan kebersamaan pada masyarakat dalam memenuhi standar gizi dengan cara yang lebih ekonomis. Berdasarkan observasi dalam kegiatan ini menunjukkan bahwa masyarakat telah memahami manfaat tanaman kelor serta mampu mengolahnya menjadi berbagai produk pangan bergizi. Simpulan: Kegiatan pengabdian berupa edukasi dan demonstrasi langsung tentang pemanfaatan daun kelor terbukti memberikan dampak positif terhadap peningkatan kesadaran gizi dan keterampilan masyarakat dalam memanfaatkan kelor sebagai sumber pangan lokal yang ekonomis dan berkelanjutan untuk pencegahan stunting. Melalui edukasi gizi, pelatihan pengolahan pangan berbasis kelor memberikan motivasi dan perubahan perilaku masyarakat untuk konsumsi makanan yang lebih sehat dan menciptakan ketahanan pangan keluarga. Saran: Meskipun keberlanjutan program masih memerlukan pendampingan dan monitoring, diharapkan program SAKURA atau program edukasi yang serupa dapat menjadi model intervensi gizi berbasis masyarakat yang efektif dalam menurunkan risiko stunting dan meningkatkan kesehatan keluarga.